Psychological Contract Breach: Consequences of Unkept Promises of Permanent Employment - Ahmed, E.; D'Netto, Brian; Chelliah, J.; Fein, E. (Academy of Taiwan Information Systems Research, 2015)
Adopting a psychological contract perspective, this study examines attitudinal and behavioral reactions of temporary employees to repeated broken promises of permanent employment by their employers. Data were collected through self-report and co-worker rating surveys from 140 bank employees in Bangladesh. To identify psychological contract breaches and employees’ reactions, the data were analyzed using correlations and regressions. Past research has focused mainly on the organizational benefits of using temporary employees. In contrast, the results of our empirical study indicate that the continuous extension of involuntary temporary status resulted in lower self-reported and co-worker-rated organizational citizenship behaviors, higher self-reported and co-worker ratings of job neglect, and increased turnover intentions. The implications of a psychological contract breach in terms of managing a temporary workforce are also discussed. The findings present new knowledge of the attitudinal and behavioral consequences arising from employers’ failure to honor their promise of permanent employment to long-term temporary employees. This research will be of particular interest to employers, employee advocates, human resource management practitioners, and academics in the field of management. However, the results cannot be generalized to all industry sectors or all types of temporary employees as the study covered temporary employees in the banking sector only.